Carotid artery doppler study in patients of myocardial infarction and its correlation with other atherosclerotic risk factors: A cross-sectional study - Somani K; Gupta P; Pisal T (Journal of Medical and Scientific Research)
Background: Carotid Doppler (CD) findings, including stenosis, increased carotid intima-media thickness (CIMT) and plaques, are linked to a higher risk of myocardial infarction (MI). Atherosclerotic risk factors play a key role in these changes. However, limited research has examined the association of these CD characteristics with risk factors in Indian patients with MI. This study evaluated the association of atherosclerotic risk factors with CD findings and the association between CIMT and coronary angiography (CAG) findings in MI patients.